Debt Position in Illegal Online Loans - Fathni, Indriya; Harsya, Rabith Madah Khulaili; Hasibuan, Kalijunjung; Basri, Basri; Mas’ud, Fadil (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
This research is a qualitative research with a descriptive normative approach, namely explaining the Position of Debt in Online Loans in the Indonesian legal system in descriptive form and accompanied by legal arguments. The data used are secondary data that researchers obtain from credible sources, namely websites, books, scientific journals, and others that are commonly used in every study. The data are analyzed by stages of data collection, data sampling, data reduction, and drawing conclusions. The result in this article show that the borrower is still obliged to return the loan that has been borrowed without being burdened with anything outside of the debt that could burden the borrower.